"If we can't call it the mfecane, then what can we call it?": Moving the debate forward - Wright, John (My University, 1994)
The mfecane as fetish: In the last six years a major controversy has blown up among historians of southern Africa about the historical reality or otherwise of the phenomenon commonly known as the mfecane (1). Since it was first popularized by John Omer-Cooper in his book The Zulu Aftermath, published in 1966,(2) the term has become widely used as a designation for the wars and migrations which took place among African communities across much of the eastern half of southern Africa in the 1820s and 1830s. For more than a century before Omer-Cooper wrote, these upheavals had been labelled by writers as 'the wars of Shaka' or 'the Zulu wars'; today the view remains deeply entrenched among historians and public alike that the conflicts of the period were touched off by the explosive expansion of the Zulu kingdom under Shaka. In a chain reaction of violence, so the story of the mfecane goes, warring groups carried death and destruction from the Zululand region southwards into Natal and the eastern Cape, westward onto the highveld, and northwards to the Limpopo river and beyond. The violence came to an end only when most of the communities which had managed to survive the supposed chaos of the times had been amalgamated into a number of large defensive states under powerful kings.
African Studies Seminar series. Paper presented 29 August 1994
Keywords: Bantu-speaking peoples. Migrations; Africa, Southern. History. Mfecane period, 1816-ca. 1840